Two new records of worm or spaghetti eel genus Moringua (Anguilliformes: Moringuidae) from estuaries and lagoons in Vietnam - Vo, Van Quang; Huans-Ching, Ho; Hibino, Yusuke (Vietnam Journal of Marine Science and Technology, 2025)
During a survey of central Vietnam estuaries and lagoons, 82 specimens of two newly recorded worm eels species, Moringua microchir Bleeker, 1853 and Moringua raitaborua (Hamilton, 1822) for Vietnam were collected and their morphometric and meristic details were recorded. Moringua microchir is characterized by a body depth of 30–44.5 in total length (TL), head length (HL) 8.7–10.7 in TL, anus far behind mid-body, distances from the tip of snout to the anus 1.5–1.6 in TL, pectoral fin small and rudimentary, 10.6–30.5 in HL, and total vertebrae 105–108. Moringua raitaborua is distinguished by a body depth of 26.7–40.9 in TL, HL 7.4–8.7 in TL, rictus before the posterior margin of the eye, pectoral fin small, but not rudimentary, 3.3–5.8 in HL and total vertebrae 102–104. Morphological variations occur in the ontogenetic stage and they differ significantly in appearance at different growth stages. This discovery suggests that these two species have broader distributions in Vietnam.